Confusion and learning in the voluntary contributions game - Ralph-C. Bayer; Elke Renner; Rupert Sausgruber (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
We use a limited information environment to assess the role of confusion in the repeated voluntary contributions game. A comparison with play in a standard version of the game suggests, that the common claim that decision errors due to confused subjects biases estimates of cooperation upwards, is not necessarily correct. Furthermore, we find that simple learning cannot generate the kind of contribution dynamics commonly attributed to the existence of conditional cooperators. We conclude that cooperative behavior and its decay observed in public goods games is not a pure artefact of confusion and learning.
Keywords: C90; D83; H41; 330; voluntary contribution mechanism; public goods experiments; learning; limited information; confusion; conditional cooperation